Enhancement of Anime Imaging Enlargement using Modified Super-Resolution CNN - Tanakit Intaniyom; Warinthorn Thananporn; Kuntpong Woraratpanya (My University, 2021)
Anime is a storytelling medium similar to movies and books. Anime images are a kind of artworks, which are almost entirely drawn by hand. Hence, reproducing existing Anime with larger sizes and higher quality images is expensive. Therefore, we proposed a model based on convolutional neural networks to extract outstanding features of images, enlarge those images, and enhance the quality of Anime images. We trained the model with a training set of 160 images and a validation set of 20 images. We tested the trained model with a testing set of 20 images. The experimental results indicated that our model successfully enhanced the image quality with a larger image-size when compared with the common existing image enlargement and the original SRCNN method.
Keywords: Anime; Advanced Image Processing Techniques